Real world treatment and clinical outcomes of diabetic macular edema at Charlotte Maxeke Johannesburg academic hospital (CMJAH), a six month study - Mothekhe, Priscilla (My University, 2022)
Aim : To evaluate the six months treatment patterns and clinical outcomes of DME management in a real world setting at a South African central hospital Methods: A retrospective analysis of DME patients treated with bevacizumab from 1 September 2018 to 31 October 2019. Patients were required to have been followed up for six months. Results: A total of 127 records of patients were evaluated. Thirty-two eyes of 22 patients met the inclusion criteria. At six months the median visual acuity (VA) change in the loading dose group was 0.1 logMAR (p = 0.2) and 0.1 logMAR (p = 0.152) in the non-loading dose group, both not statistically significant. Central foveal thickness (CFT) was significantly reduced in the loading dose group but not in the non-loading dose group, 18% (p = 0.038) vs 6% (p = 0.678) respectively. The mean number of injections were 4,7 (SD = 1,87) in the unilateral eye injection group and 5.2 (SD = 1.94) in the bilateral eye injection group. Conclusion: In a real-life clinical setting, intravitreal bevacizumab improved visual acuity and anatomical outcomes in patients with diabetic macula oedema. Compared to major clinical trials, lower visual acuity gains and less frequent intravitreal injections were observed.
A research report submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022